Maternal mortality reduction: a need to focus actions on the prevention of hypertensive disorders of pregnancy - Belizan, Jose (2021)
Maternal mortality (MM) reflects one of the most striking global health inequalities. Global figures of MM fell significantly from 1990 to 2017. The reduction was largely due to a 70% fall in haemorrhages, and a limited (18.2%) improvement in hypertensive disorders of pregnancy (HDP). If this trend continues, by 2021 HDP will be the main cause of global MM. MM reductions due to haemorrhage is reassuring, however MM due to HDP show a more complex situation as early detection of HDP requires regular contact of pregnant women with the health system. In order to reduce MM due to HDP, population wide preventive actions such as low dose aspirin and adequate calcium intake are required, especially in areas where women have little contact with the health systems. Calcium supplementation for women with low calcium intake has reduced the risk of pre-eclampsia, with further reductions starting daily supplementation with 500 mg of calcium preconceptionally, however adherence to supplementation is limited. To reduce global inequities in calcium intake and consequently in the HDP, food fortification seem to be an attractive strategy to achieve an increase of calcium intake.